Education in virtual environment - Banek Zorica, Mihaela (Array, 2009)
Students are our most precious resource, and as such should be cultivated with the utmost care in well-designed educational environments. If our goal is to assist the learner in developing the knowledge, skills, and attitudes to join society as a functioning member, we should be oriented towards the future creating successful learning systems. Virtual environment potentially provides such a interesting, instructive, interactive environment also for students in Croatia, but there are some possible detrimental educational consequences. Anyone who is engaged in education must be aware that many of the necessary skills people learn through direct interaction with others even without technological intermediaries. This paper will give a general overlook on the characteristics of education in virtual worlds, give insight in pilot study on implementing virtual world in university classes and discuss both positive and negative sides of education in virtual environment.